Definition, Dimensions, and Research Methods of User Experience - Xiong Ding; Teddy Marius Soikun (Human Resource Management Academic Research Society (HRMARS), 2023)
UX (User Experience) is a complex concept. In order to clearly explain its connotation, this study will review the theoretical and practical content of UX from the definition, dimensions, elements, and aspects of UX. Furthermore, this paper reviews the research methods adopted by scholars since the concept of UX was proposed. Although this article has some omissions and does not sort out all the scholars' views, it has included the main views in this field of research.